MODEL DESAIN GAYA BELAJAR DAN KREATIVITAS SISWA SD BERDASARKAN METODE FORWARD CHAINING - Nur Alamsyah; Rayung Wulan; Achmad Sarwandianto; Aulia Ar Rakhman A (IST AKPRIND Yogyakarta, 2018)
Design model on this research based learning style questionaire of 66 items that consist of 22 statements it is taken from learning style questionaire of visual, auditorial and kinestetic and the learning creativity consist of 48 items. Learning style is a way when students accepting the process of learning, it is very important to be studied with the aim of helping students understand the learning model of interest in the learning process because it is very effected on the result obtained by students. The valicity test is used for learning style questionaire learning creativity, the testing for consist of internal consistency, determining the item instrument, and reliability. The validity test for questionaire is by using content validity. Validator for both questionaire is the actual output from the forward chaining method. There are go students who chose to be the respondents of learning stlye questionaire and 64 students became the respondent of learning creativity questionaire. There are 45 items that ful fill requirement , 15 items represent the learning style questionaire of visual, auditorial, kinestetic and learning creativity. It is shown that there 35 items require the test and the assesment of forward chaining method. The forward chaining method has the actual result in validity test and used in search technique, then by integrating actual information with the result of validity test of questionaire. Based on the calculation result, reliability questionaire creativity studied index obtained for 0.88. It shows that the questionaire instrument of students’s learning creativity meets the criteria reliable and feasible to be used with forward chaining method.